A brief history of intelligence : evolution, AI, and the five breakthroughs that made our brains - Bennett, Max S. (Max Solomon) (New York : Mariner Books, 2023)
"In the last decade, the science of understanding the human brain and replicating its most complicated processes through artificial intelligence has grown exponentially. Intricate neurological functions ranging from writing poetry to crafting original articles, arenas that had long been thought of as science fiction, have become our reality. And yet, large gaps remain in what AI can achieve-gaps that, as pioneering artificial intelligence entrepreneur Max Bennett argues compellingly, exist because there is still too much we don't understand about our own brains. Finding these answers requires diving into the long billion-year history of how animal brains emerged from matter; a history filled with countless half-starts, calamities, opportunities, and clever innovations. Not only do our brains have a story to tell-in fact the future of AI depends on it. Now, in A Brief History of Brains, Bennett bridges the gap between neuroscience and AI to tell the brain's evolutionary story, while demonstrating how understanding that story will shape the next generation of great AI breakthroughs. Deploying fresh perspective and lively storytelling, Bennett sheds long overdue light on evolutionary neuroscience, a historically small scientific field that holds the keys to the biggest secrets in AI. Working with support from many of the top minds in the field, Bennett consolidates four billion years into an approachable new model, identifying the Five Breakthroughs that mark the brain's most important evolutionary leaps. As we go back further in time, brains get much simpler and behavior gets much simpler, making it easier to understand these ancient brains and the complexity that emerges at each subsequent iteration. As each breakthrough brings new insight to the biggest mysteries of human development, it also contains fascinating corollaries to developments in AI, showing where our technological skill has matched the brain's evolution and where the missing links continue to hold us back. Indeed, until we understand and embrace every part of our brain's journey, parts of AI-including ones that we need to grow and evolve-will remain elusive. Endorsed and lauded by the brightest and best neuroscientists in the field today, Bennett's work synthesizes the most relevant scientific knowledge and cutting-edge research to create an easy-to-understand and riveting evolutionary story. With sweeping scope and stunning insights, A Brief History of Brains proves that understanding the arc of our brain's history can unlock the tools for successfully navigating our technological future"--
The world before brains -- The birth of good & bad -- The origin of emotion -- Associating, predicting, & the dawn of learning -- The Cambrian explosion -- The taming of time -- The problems of patterns -- When life got curious -- From 1D to 4D -- The neural dark ages -- The neocortical mystery -- Mice in the imaginarium -- The invention of intent -- The great embodiment -- The model of minds from the ashes of space dust -- How "theory of mind" might work -- Monkey see, monkey do -- Anticipating future needs -- The search for human uniqueness -- Language in the brain -- The perfect storm -- A window with nothing on the other side.
Includes bibliographical references (pages 373-402) and index.
Keywords: Brain -- physiology; Biological Evolution; Artificial Intelligence; Intelligence -- physiology